The Ambiguity of Interpretation: Distinguishing Interpretation from Construction - Peter M. Tiersma (Washington University Law Quarterly, 1995)
One might expect that linguistics-the scientific study of language- would have much to offer the legal profession, which is so often occupied with the interpretation of legal texts. That possibility was evidently the point of departure for this conference. Those reading the proceedings will, however, be struck by how linguists and legal scholars employ quite different discourses about language, especially when it comes to meaning and interpretation.
Keywords: Linguistics; Law – Interpretation & amp; construction